Milano 1923-1936. Tre guerre contro la misura dialogica (ACME, 2021)
Milan experienced three devastating wars over forty years 1943-1944’s “war from the sky” destroyed a quarter of its housing stock, yet the other two conflicts affected the city dramatically. First of all, Fascism contributed to the demolition of more than 135,000 living spaces in the historic centre. Such depletion was then completed in the years of Reconstruction and economic boom. Fascism pursued two objectives by wreaking havoc on the city centre: to drive the working classes away from the centre and to make room for directional and financial activities. According to the political and urban strategists who were concerned, historical city patterns impeded proper traffic regulation and were responsible for the outbreak of disease and moral degeneration. As History demonstrates, Urban planning can thus become an accomplice and implementer of the design of the regime.During Reconstruction, historical urban features and patterns who were addressed inadequately also due to poor judgment about “how to make a city”. As a consequence, except for the creation of public initiative districts, there will be substantial continuity with the pre-war urban planning policy.